FRI0413 THE ASSOCIATION OF OBESITY WITH OSTEOARTHRITIS IS LIMITEDLY MEDIATED BY HYPERTENSION AND SUBCLINICAL ATHEROSCLEROSIS. (2nd June 2020) - Loef, M.; Van der Geest, R. J.; Lamb, H. J.; De Mutsert, R.; Rosendaal, F.; Kloppenburg, M.
Abstract : Background: Obesity-related metabolic dysregulation may lead to atherosclerotic vascular changes. It has been hypothesized that a compromised blood flow may cause detrimental changes to the subchondral bone and decrease nutrient supply to the cartilage. To which extent atherosclerosis may explain the association between obesity and OA has not been investigated. Objectives: To investigate the role of hypertension and subclinical atherosclerosis (carotid intima-media thickness (IMT), popliteal vessel wall thickness (VWT), aortic pulse wave velocity (PWV)) as mediators of the association of obesity with hand and knee OA. Methods: We used cross-sectional data from the population-based NEO study, excluding participants with concomitant rheumatic diseases (n = 323), resulting in 6, 334 participants. Clinical hand and knee OA were defined by the ACR classification criteria. Popliteal VWT was assessed on MR images in a subpopulation (n = 1, 095), using VesselMASS for semi-automated detection of the vessel wall boundaries. Aortic PWV was estimated on abdominal velocity-encoded MR images in a subpopulation (n = 2, 580). Carotid IMT was assessed by ultrasonography. Hypertension was defined as a systolic blood pressure ≥ 130 mmHg or a diastolic blood pressure ≥ 85 mmHg, or using antihypertensive medication. Continuous variables were standardized (mean 0, standard deviation 1). Associations between BMI and OA were assessed with logistic regression analyses, adjusted for age, sex and education. Subsequently, possible mediators were added to the model and the percentage mediation was calculated. Results: The population consisted of 55% women, with a mean (SD) age of 56 (6) years and BMI of 26 (4) kg/m 2 . Hand OA was present in 8% and knee OA in 10% of participants. Hypertension was present in 61.6% of participants. Mean (SD) carotid IMT was 0.62 (0.09) mm, popliteal VWT was 0.53 (0.05) mm, and aortic PWV was 6.56 (1.30) m/s. BMI was associated with the presence of hand OA and knee OA (table 1 ). BMI was positively associated with hypertension and carotid IMT, but not with popliteal VWT and aortic PWV. The association between BMI and hand OA was partially mediated by hypertension (5.9%) and carotid IMT (10.6%). Hypertension (4.9%) showed a weak mediating effect for the association between BMI and knee OA. Conclusion: We assessed whether the association between BMI and OA was mediated by hypertension and atherosclerosis. Our results imply that either such mediation is absent or trivial, or that the atherosclerosis measures were too weak. Disclosure of Interests: None declared